Studying Loneliness Feeling Ratio in Hyperactive Children and Children with Autism - Oliaei, Farideh (International Journal of Psychosocial Rehabilitation, 2020)
Loneliness feeling in children indicates the failure and weakness of interpersonal relationships with peers, which leads to dissatisfaction with social relationships with other children. The main purpose of the present research is to investigate the difference between loneliness feeling ratio in hyperactive children and children with autism. The present research is applied in terms of purpose. Also, the present research is descriptive of causal-comparative researches type that compares the ratio of frustration, social acceptance and loneliness feeling in hyperactive children and children with autism in Bandar Abbas. The statistical population of the research includes all hyperactive children and children with autism in Bandar Abbas. With regard to access to the sample size, the number of sample size of the research is 30 people that were divided into two hyperactive and autism groups of 15 people. To test the hypotheses, by applying SPSS software, mean difference tests were used. The obtained results showed that the significance level of loneliness feeling variable is lower than 0.05, and this indicates a significant difference of these variables between hyperactive children and children with autism.